2018
DOI: 10.1002/piq.21267
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and Communication as Antecedents of Shared Mental Models Emergence

Abstract: The effect of leadership on shared mental‐model emergence was investigated in the current study. In an experimental setting, 44 2‐, 3‐, and 4‐person teams (N = 129) working on a complex building‐block task were assigned to one of three leadership manipulations (inspirational motivation, intellectual stimulation, control). Team sessions were video recorded, and intra‐group communication patterns were coded. We found that leadership style influenced intra‐group communication patterns. Furthermore, leadership sty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…SMM are an essential component of effective teamwork (Boies & Fiset, 2018; DeChurch & Mesmer-Magnus, 2010a; Mohammed et al, 2010). Narrative reviews (e.g., Mohammed et al, 2010) and meta-analytical evidence (e.g., DeChurch & Mesmer-Magnus, 2010a; Mesmer-Magnus et al, 2017; Niler et al, 2021; Turner et al, 2014) support the benefits of SMM as a key determinant of team processes (e.g., goal setting), emergent states (e.g., collective efficacy), and outcomes (e.g., performance).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SMM are an essential component of effective teamwork (Boies & Fiset, 2018; DeChurch & Mesmer-Magnus, 2010a; Mohammed et al, 2010). Narrative reviews (e.g., Mohammed et al, 2010) and meta-analytical evidence (e.g., DeChurch & Mesmer-Magnus, 2010a; Mesmer-Magnus et al, 2017; Niler et al, 2021; Turner et al, 2014) support the benefits of SMM as a key determinant of team processes (e.g., goal setting), emergent states (e.g., collective efficacy), and outcomes (e.g., performance).…”
Section: Discussionmentioning
confidence: 99%
“…Several decades of research supports the scientific and organizational relevance of SMM for effective teamwork (Boies & Fiset, 2018; Cannon-Bowers & Salas, 2001; DeChurch & Mesmer-Magnus, 2010a; Mesmer-Magnus et al, 2017; Mohammed et al, 2010; Turner et al, 2014). Yet absent from the scientific literature is an integrative understanding of the ways by which SMM have been and can be enhanced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, when teachers trust that principals have sufficient talent, helpfulness, and honesty, which are the determinants of inclusive leadership, their perception of the inconsistency between what the school administration says and does decreases. Studies have shown that trust in principal has a mediating role in the effect of principal leadership styles on teachers' positive attitudes (e.g., Bektaş et al, 2020;Bellibaş & Gümüş, 2021;Boies & Fiset, 2018;Hallinger et al, 2017;Karacabey et al al., 2022;Kılınç et al, 2022;Ma & Marion, 2019). Related research findings support the relationship between trust in principal and inclusive leadership behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…First, research has emphasized the importance of intragroup communication for maintenance of shared mental models (e.g., He, Butler, & King, 2007; Kennedy & McComb, 2010). Boies and Fiset (2018) found that through intellectual stimulation and inspirational motivation, leaders were successful in building shared mental models through the mediating effect of task- and team-related communication. In support, in our review of virtual teams, we noted the recurrent finding of a relation between the amount of communications and perceptions of leadership (Piccoli et al, 2004; Tyran et al, 2003; Yoo & Alavi, 2004).…”
Section: Model Developmentmentioning
confidence: 99%